Volantis (2017)
In Colombia, there are many low income athletes with unfavorable economic resources that do not have affordable essential tools for their training process. Volantis is a sport brand proposal that recognizes this problem, and offers an option of specialized footwear as a solution. In this way, Volantis, through a business strategy, provides an affordable and easy-to-access product designed to encourage an adequate sport development in Colombia's athletics.